Synthesis, molecular docking and antimicrobial evaluation of octadecanoic acid [4-(5-phenyl-4,5-dihydro-1H-pyrazol-3-yl)phenyl]-amide pyrazoline derivatives (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A new series of octadecanoic acid [4-(5-phenyl-4,5-dihydro-1H-pyrazol-3-yl)phenyl]-amide pyrazoline derivatives were designed synthesized, and characterized by spectral analysis (IR, MS, 1H-NMR, 13C-NMR). The compounds were screened for in vitro antibacterial activity against Escherichia coli and Staphylococcus aureus. All the compounds exhibited significant antibacterial activity with minimum inhibitory concentrations ranging from 1.2 to 2.5 mg/mL. The newly synthesized compounds were also found to have good anti-fungal activity against Fusarium oxysporum and Penicillium italicum, with all the compounds showing MIC of 2.5 mg/mL for both the fungal strains. Molecular docking studies were also incorporated to elucidate the possible interactions of the synthesized compounds with bacterial and fungal proteins.